Znaczenie relacji przywiązania w cyklu życia człowieka. Analiza wybranych aspektów bliskich relacji - Matysiak-Błaszczyk , Agata; Jankowiak, Barbara (Studia Edukacyjne, 2020)
The article analyzes the significanceof attachment relations for the ability to enter into close relations in the human life cycle. The secure attachment style which develops on the basis of the primordial relation between mother (or a guardian) and the child in the firststages of life is the cornerstone of future intimate relations and a resource which facilitates successful dealing with developmental tasks in interpersonal dependency relations. During the childhood, it contributes to the development of the relation of trust and dependence, during the adolescence to the growth of new extra-family relations and in adulthood to the co-creation with the partner of an intimate love relationship.